Replica of Bionic Nepenthes Peristome-like and Anti-Fouling Structures for Self-Driving Water and Raman-Enhancing Detection - Lin, Yen-Ting; Wu, Chun-Hao; Syu, Wei-Lin; Ho, Po-Cheng; Tseng, Zi-Ling; Yang, Ming-Chien; Lin, Chin-Ching; Chen, Cheng-Chen; Chen, Cheng-Cheung; Liu, Ting-Yu (Polymers, 2022)
The flexible, anti-fouling, and bionic surface-enhanced Raman scattering (SERS) biochip, which has a Nepenthes peristome-like structure, was fabricated by photolithography, replicated technology, and thermal evaporation. The pattern of the bionic Nepenthes peristome-like structure was fabricated by two layers of photolithography with SU-8 photoresist. The bionic structure was then replicated by polydimethylsiloxane (PDMS) and grafting the zwitterion polymers (2-methacryloyloxyethyl phosphorylcholine, MPC) by atmospheric plasma polymerization (PDMS-PMPC). The phospholipid monomer of MPC immobilization plays an important role; it can not only improve hydrophilicity, anti-fouling and anti-bacterial properties, and biocompatibility, but it also allows for self-driving and unidirectional water delivery. Ag nanofilms (5 nm) were deposited on a PDMS (PDMS-Ag) substrate by thermal evaporation for SERS detection. Characterizations of the bionic SERS chips were measured by a scanning electron microscope (SEM), optical microscope (OM), X-ray photoelectron spectrometer (XPS), Fourier-transform infrared spectroscopy (FTIR), and contact angle (CA) testing. The results show that the superior anti-fouling capability of proteins and bacteria (E. coli) was found on the PDMS-PMPC substrate. Furthermore, the one-way liquid transfer capability of the bionic SERS chip was successfully demonstrated, which provides for the ability to separate samples during the flow channel, and which was detected by Raman spectroscopy. The SERS intensity (adenine, 10−4 M) of PDMS-Ag with a bionic structure is ~4 times higher than PDMS-Ag without a bionic structure, due to the multi-reflection of the 3D bionic structure. The high-sensitivity bionic SERS substrate, with its self-driving water capability, has potential for biomolecule separation and detection.